Textbooks as Value-laden: A Critical Discourse Analysis of Moral Values Representation in Primary School EFL Textbooks - Sitio, Ihsan Tanama; Sinar, T. Silvana; Rangkuti, Rahmadsyah (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
The inculcation of moral values in English textbooks, particularly in primary schools, has been a global concern in recent decades due to English’s growing importance as a global lingua franca and the impact it carries. Hence, the present study aimed to: (1) elucidate the realisation of moral values discursively represented in three primary school English textbooks entitled English Chest 1, 2 and 3, and (2) determine the extent of the textbooks’ contents in teaching the moral values. Fairclough’s (1995, 2013) framework of Critical Discourse Analysis (CDA) integrated with Kress & Van Leeuwen’s (2006) Visual Grammar Theory (VGT) was applied to elucidate the depiction of moral values in the textbooks. Additionally, Isaacs’ (2001) framework of Developmental Moral Values and Smetana’s (2006) Social Domain Theory were also adopted to look at how the contents of the textbooks teach moral values. The results show that (1) modesty (8,99%), curiosity (8,44%), perseverance (7,08%), and friendship (6,53%) are the most frequently occurring values in the three EFL textbooks. (2) The discursive realisation has revealed that certain fundamental moral values such as audacity, sociability, industriousness, respect for others, and responsibility are taught through the depictions of verbal-visual images in both school and familial contexts. Importantly, the three EFL textbooks have fairly adhered to the Indonesian moral (character) education goals and stipulation. They also provide implications on both primary school students and English teachers’ pedagogical, linguistic, and moral development so as to raise EFL textbook designers’ awareness to develop more morally-laden content.